Do patient characteristics influence efficacy and renal outcomes in liver transplant patients receiving everolimus?. Issue 3 (6th February 2016) - De Simone, Paolo; Saliba, Faouzi; Dong, Gaohong; Escrig, Cesar; Fischer, Lutz
Abstract: Data from the 24‐month randomized, multicenter, open‐label H2304 study in 719 de novo liver transplant recipients were analyzed to evaluate the influence of variables potentially affecting immunological or renal response: recipient age, gender, end‐stage disease, hepatitis C virus (HCV) status, and Model for End‐stage Liver Disease score and estimated glomerular filtration rate (eGFR) at randomization (day 30). Treated BPAR was similar between everolimus with reduced tacrolimus (EVR + Reduced TAC) vs. conventional tacrolimus‐based therapy (TAC Control) in all subpopulations, with a trend to lower risk under everolimus with reduced tacrolimus (EVR + Reduced TAC) in patients <60 yrs and HCV‐negative recipients. Risk of graft loss or death was similar in both treatment groups for all subpopulations. The change in eGFR to month 24 showed a benefit for EVR + Reduced TAC vs. TAC Control in all subpopulations other than those with the lowest baseline eGFR (30 to <55 mL/min/1.73m 2 ), with a significant difference in favor of EVR + Reduced TAC for younger recipients (<60 yr), female patients, HCV‐negative patients and those with baseline eGFR of 55 to <70 mL/min/1.73 m 2 . Everolimus with reduced tacrolimus maintains efficacy to at least two yr after liver transplantation even in patients with risk factors for rejection, with particular renal benefits in specific patient subpopulations.